Challenges in Developing Integrated Halal Industry in Indonesia - Mohammad Iqbal Irfany (Halal Tourism and Pilgrimage, 2022)
This study aims to determine the opinions and recommendations of experts regarding the problems of the integrated halal industry in Indonesia to determine the priority of the most important variables to be fixed first. This research was conducted in September 2020 using primary data obtained from interviews of experts consisting of academics, practitioners and regulators with a background in sharia economics. The data were analyzed by the Delphi method to find the main priority and agreed upon convergence by experts. The results showed that of the 6 criteria for integrated halal industry problems in Indonesia, there are 22 variables with convergent-convergent consensus based on expert opinion and only 2 variables with Divergent consensus. The 3 main priority problems of the integrated halal industry in Indonesia along with the problems in the sub-criteria are (1) Regulation & Policy: Implementation, (2) Information Technology & Services: Accessibility, (3) Public Awareness: Socialization. This research can be used by readers to make improvements in the halal industry system in Indonesia with priorities according to the findings of this study. This research is the first research to comprehensively calculate the expert's assessment regarding the integrated halal industry problem in Indonesia using the Delphi method and its priority recommendations.